Pancho Villa - Savalas, Telly; Walker, Clint; Francis, Anne.; Connors, Chuck; Martin, Eugenio (South Plainfield, New Jersey The Congress Video Group, 1934)
The only man ever to invade the United States was--Pancho Villa! The famous-or infamous--Mexican revolutionary held the border town of Columbus for a few hours. This man who could neither read nor write, famed for his bravery, feared for his unspeakablecruelty, became the legendary bandit-hero of a nation and his name became the symbol under which delirium, savagery and the confusion of those times were focused. Telly Savalas, one of the screen's most versatile and brilliant performers, reaches the pinnacle of an outstanding career in his role as " Pancho Villa." Pursued by both the Mexican and United States Army ( led by General Pershing). Villa outwitted his pursuers across a thousand miles of hostile terrain to ride into legend, the cry of " Viva Villa" still ringing in his ears.
Summary taken from cover.
Screenplay writer, Julian Zimet ; Cinematographer, Alejandro Ulloa ; Music, Anton Garcia Abril.
Telly Savalas, Clint Walker, Anne Francis, Chuck Connors.
VHS.
Gift
English
Keywords: Bandit -- Adventure; United States army -- Action; Mexico -- USA; Mexican Revolution -- Mexico; Biographical films; Historical films; Feature films; Independent films